2020
DOI: 10.1007/s10943-020-01088-3
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Faith Perception in a Pandemic of COVID-19

Abstract: The COVID-19 pandemic has impacted religion and faith in different ways. Numerous restrictions have been implemented worldwide. Believers are in conflict with authorities’ warnings that gatherings must be limited to combat the spread of the virus. Religion has always played a role of the balm for the soul, and the regular religious participation is associated with better emotional health outcomes. In our study, we examined whether the exposure to COVID-19 enhances the faith. The instrument used was a survey ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
2
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 11 publications
10
120
2
9
Order By: Relevance
“…Also, close family and social relationships in this province could affect collective activities and norms during the COVID-19 epidemic [ 12 , 13 ]. It should be noted that the religious beliefs of Iranians and Hormozgan residents may influence stress management and mental relaxation [ 14 , 15 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Also, close family and social relationships in this province could affect collective activities and norms during the COVID-19 epidemic [ 12 , 13 ]. It should be noted that the religious beliefs of Iranians and Hormozgan residents may influence stress management and mental relaxation [ 14 , 15 ] .…”
Section: Introductionmentioning
confidence: 99%
“…These correlation patterns allow us to confirm previous hypotheses, providing additional evidence on the validity of the SCSRFQ among Peruvian youth and adults. In the case of the positive relationships between faith strength and COVID-19 anxiety, it seems to suggest that the negative pressure of the pandemic on people's mental health intensified their faith along with other religious practices, such as prayer, thus seeking to have protection against the danger of the COVID-19 pandemic (Boguszewski et al 2020;Kowalczyk et al 2020;Newport 2020). Similarly, the relationship between the latent variables life satisfaction and faith strength would indicate that the latter is a positive and cognitive indicator for maintaining well-being (Koenig 2020; Wnuk 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding religious faith, it has been suggested that it facilitates adaptation to diseases and the consequences derived from them (Kowalczyk et al 2020), becoming a factor with important effects on health and well-being . This is due to its benefits on the functioning of the immune system and vulnerability to viral infections, making the disease less severe and people have a faster recovery (Koenig 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It contained three main sections that address questions on the fear of COVID-19, Spirituality, and stigmatization. The online google form has been used previously by many researchers on studies of this nature ( Lucchetti et al., 2020 ; Rias et al., 2020 ; Kowalczyk et al., 2020 ). The study was conducted in Lagos, Ogun, Oyo, Osun in the southwest part of Nigeria.…”
Section: Methodsmentioning
confidence: 99%